Indigenous African Language Media
XXXVI, 444 p. 11 illus., 6 illus. in color.
Keywords: The book contributes to the sparse academic literature on African and minority language media research. It serves as a compendium of experiences, activities and case studies on the use of native language media. Chapters in this book make theoretical, methodical and empirical contributions about indigenous African language media that are affected by structural factors of politics, technology, culture and economy and how they are creatively produced and appropriated by their audiences across African cultures and contexts. This book explores indigenous African language media about media representations, media texts and contents, practice-based activities, audience reception and participation, television, popular culture and cinema, peace and conflict resolution, health and environmental crisis communication, citizen journalism, ethnic and identity formation, beat analysis and investigative journalism, and corporate communication. There are hardly any similar worksthat focus on the various issues relating to this body of knowledge. The book provides a valuable companion for scholars in various fields like communication, media studies, African studies, African languages, popular culture, journalism, health and environmental communication. Phillip Mpofu, DLitt et Phil, is an Extraordinary Researcher at North West University, Mafikeng Campus, South Africa, in the Indigenous Language Media in Africa (ILMA) research entity. He is also a Senior Lecturer in the Department of Languages, Literature & Cultural Studies at Midlands State University, Zimbabwe. His research combines sociolinguistics, language politics, language policy, virtual communities and African language media. Israel Ayinla Fadipe is postdoctoral fellow in Indigenous Language Media in Africa research entity, Faculty of Humanities, North-West University, South Africa. He specialises in communication, cultural and gender studies, and has published articles and chapters in both local and international journals. He graduated from the Department of Communication and Language Arts, University of Ibadan, with BA in Creative Writing, MA in Popular Music and PhD in Applied and Gender Communication. Thulani Tshabangu is an emerging academic who holds a PhD in Journalism from Stellenbosch University in South Africa. He is currently a post-doctoral fellow at North West University research institute of Indigenous Languages Media in Africa where he researches about democracy and development communication in Africa; the management and political economy of African media. .